Comparing the Learning Experience of Student LED CBL (S-CBL) and Instructor Led CBL (I-CBL) in BDS Clinical Years: Case Based Learning in Dentistry - Khaleeq, Fatima; Zulfiqar, Rida; Naz, Asma; Bibi, Tauqeer; Zubairi, Atif; Khalid, Arsalan (Pakistan Journal of Health Sciences, 2025)
Literature suggests that in instructor led CBL, where clinical cases are delivered by the facilitators, student’s ability to view the authentic context of oral diseases from multiple sources of real world is hampered. Objective: To compare the level of satisfaction regarding instructor led CBL (I-CBL) and student led CBL (S-CBL) of dental students in their clinical years and the test exam score of dental students gone through instructor led CBL (I-CBL) and student led CBL (S-CBL). Methods: Comparative cross-sectional study was carried out at Bahria Dental College Karachi for 1 year after approval of synopsis. Non-probality Sampling Technique was used for sample collection. Inclusion criteria included dental students in five clinical rotations for two months and students who provided consent to participate in study. Data were analyzed using SPSS version 25.0 and chi square test was applied. Results: Among total subjects 22% were females and 78% were males. Both S-CBL and I-CBL received high ratings for satisfactory sessions, but S-CBL participants (69%) experience was slightly higher, that indicated a preference for the student-led approach. Prioritized teaching method using it was recommended by 65% of the students, especially in clinical years of dentistry. Conclusions: It also brought students and faculty together to create a healthy communication flow. A strong preference for CBL as a better learning strategy especially for clinical knowledge was found among many dental institutions by dental undergraduates. PBL was also recommended by many students in problem solving, communication skills and sharpening critical thinking.